THE SPATIAL IMAGINATION IN EDUCATION OF PRIMARY SCHOOL - TOMKOVA, Viera (Trends in education, 2012)
In the era of implementation of the ICT into the educational process it is increasingly probable that our pupils get familiar with various graphic programs while learning. In the process of creation of graphic visualizations is expected so that students have sufficiently developed spatial awareness and they can work imaginary with objects and create newobjects, too.
Keywords: spatial imagination; technical education; the perception of space.